2015
DOI: 10.1007/s12263-015-0465-3
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory receptor genes cooperate with protocadherin genes in human extreme obesity

Abstract: Worldwide, the incidence of obesity has increased dramatically over the past decades. More knowledge about the complex etiology of obesity is needed in order to find additional approaches for treatment and prevention. Investigating the exome sequencing data of 30 extremely obese subjects (BMI 45–65 kg/m2) shows that predicted damaging missense variants in olfactory receptor genes on chromosome 1q and rare predicted damaging variants in the protocadherin (PCDH) beta-cluster genes on chromosome 5q31, reported in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Besides, OR2AK2 , a member of olfactory receptor genes family which located in chromosome 1q, involved in both GPCR signaling pathway and olfactory signaling pathway. It has been found that the predicted damaging missense variants in olfactory receptor genes on chromosome 1q and rare damaging variants in protocadherin beta-cluster genes on chromosome 5q31 co-localized in subjects with extreme obesity (Mariman et al, 2015 ). The functions of other genes in terms of obesity were unknown, whereas they may be interesting potential candidates for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, OR2AK2 , a member of olfactory receptor genes family which located in chromosome 1q, involved in both GPCR signaling pathway and olfactory signaling pathway. It has been found that the predicted damaging missense variants in olfactory receptor genes on chromosome 1q and rare damaging variants in protocadherin beta-cluster genes on chromosome 5q31 co-localized in subjects with extreme obesity (Mariman et al, 2015 ). The functions of other genes in terms of obesity were unknown, whereas they may be interesting potential candidates for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Smell perception of food affects food choices and consumption, as well as appetite and satiety signals (Yeomans, ). Mariman et al () demonstrate that there is synergistic effect between the genetic variation of OR and the predisposition of extreme obesity. Thus, the manipulation of food flavor may reduce the risk of extreme obesity by controlling overeating in genetically predisposed subject.…”
Section: The Role and Mechanism Of Ectopic Olfactory Receptors In Nonmentioning
confidence: 99%
“…We recently reported a relationship between genetic variation in the clustered protocadherin genes on chromosome 5q and extreme obesity (134) . Moreover, a genetic interaction between OR genes on chromosome 1q and the protocadherin-β genes has been observed in this extreme obesity cohort (135) . Notably, food odour can stimulate appetite, food-seeking behaviour and food ingestion, but strong or prolonged exposure to a food odour can have a satiating effect (183) .…”
Section: Sensory Cilia For Odour Perceptionmentioning
confidence: 60%
“…Possibly, the penetrance of BBS gene mutations with regard to obesity is limited and/or the contribution to obesity risk depends more on rare alleles. Previously, we sequenced thirty subjects with extreme obesity (134,135) . We checked for relatively rare variants (frequency < 0·01) with a predicted damaging impact on protein function in sixty-six genes that code for proteins, which are needed for proper cilia function (online Supplementary Table S1), including the genes mentioned in Tables 1 and 2. This resulted in the identification of twenty-four variants in seventeen subjects (Table 3).…”
Section: Ift88mentioning
confidence: 99%